CLIMATE CHANGE TRENDS IN THE RED RIVER DELTA - Thi Phuong Hang, Nguyen; Hoang Long, Nguyen; Ngoc Hung, Dao (HNUE Journal of Science: Journal of Natural Sciences, 2024)
The Red River Delta (RRD) is one of the regions most significantly impacted by climate change (CC) in Vietnam. This study utilizes correlation assessment methods and regression equations to evaluate the trends of certain meteorological factors and extreme weather events during the period 1961 - 2020 in the RRD. Overall, climate factors across the region exhibit quite clear trends of change. The highest trends in annual average temperature and maximum annual average temperature are observed in the northwestern part of the RRD, especially in major cities such as Ha Noi (the increase in mean annual temperature ranges from 0.0317 - 0.0336 ºC/year). The lowest trends in these temperatures are found in coastal, island, and mountainous areas (the increase in mean annual temperature ranges from 0.0133 - 0.0224 ºC/year). The annual rainfall reports a decreasing trend at 17 out of 23 meteorological stations in the RRD, varying from -11 to 9 mm/year. Extreme weather phenomena report little significant change, with maximum daily rainfall records a decreasing trend, varying from -3.119 to 1.395 mm/year; the number of days with rainfall exceeding 50 mm also reports a decrease, varying from -0.058 to 0.017 days/year. The results of this study will serve as a basis for developing action plans to respond to CC in the RRD.